Analysis of variability in gestation length in sows and its association with litter traits at birth - Alexander Kramarenko; Olena Yulevich; Iryna Lіuta; Serhii Kramarenko (Наукові горизонти)
Gestation length is a complex polygenic trait in sows that significantly determines their productive characteristics and influences foetal development during the embryonic period. This study aimed to analyse the effects of genotypic factors (breed of the sow and sire boar) and environmental factors (year and season of farrowing) on the variability of gestation length in sows and to determine the nature of its association with litter traits at birth using a meta-analysis algorithm. The analysis was based on primary data regarding reproductive traits in the main herd of the private joint-stock company “Plemzavod “Stepnoi”, Zaporizhzhia Region, collected from 2010 to 2013. The mean gestation length for the animals in the study herd was 115.9 ± 0.04 days, with a range of 110 to 121 days. Gestation length exhibited a very low level of inter-individual variability, with a coefficient of variation of only 1.65%. Duroc sows exhibited shorter gestation lengths, lower total litter sizes, and fewer live piglets per litter at birth compared to Landrace sows (in all cases: P < 0.001). A significant influence of the sire boar’s breed on the reproductive traits of sows was established, except for gestation length and total litter size. The longest gestation lengths were recorded during the winter months, whereas the best performance in other reproductive traits was observed in the spring. Meta-analysis revealed that the “general” estimates of the phenotypic correlation coefficient between gestation length and total litter size, the number of live piglets, and total litter weight at birth were significant and negative. In contrast, the correlation between gestation length and the average birth weight of live piglets was significant and positive